Penerapan Metode User Centered Design Untuk Mengembangkan E-Learning Universitas Jember Berbasis Mobile - Fahrobby Adnan; Muhammad Huda Muttaqin; Tio Dharmawan (INFORMAL: Informatics Journal, 2018)
Aspects of usability or usability in the user's point of view when using and utilizing a product. The use of an inappropriate method in developing the design will increase the number of requests to improve the product after it is finished. Inappropriate method of selecting methods for design development Usually occurs in applications based on Graphical User Interface (GUI), e-commerce websites, cellular services, and also technology in the field of education called e-learning. E-learning is one technology that develops a distance learning system that provides a variety of solutions where the Internet is the medium. Supported by the development of technology supported by smartphones can also be used for the learning process. With the existence of smartphones, students will more easily access learning materials, and teachers will also be easier to share the material to be received. To support the effort to obtain the level of user satisfaction without leaving the specific purpose of making the application itself a user centered design (UCD) method can be applied. UCD is a method that helps users. With the application of this method users will be satisfied and comfortable when using with the system. Based on the concepts of the UCD method and the problems that occur in e-learning especially the University of Jember E-Learning application, it can be seen that the UCD method is suitable to be applied in the development of mobile-based Universitas Jember e-learning applications with the aim of making it easier students and lecturers in the learning process at the University of Jember. This research was conducted in 3 stages, namely data collection, analysis, and system development. The data collection phase consists of literature studies, and questionnaires. The analysis phase is done by processing the data from the questionnaire and conducting usability testing. The development phase is done by building a mobile-based e-learning application. The results of this study are the University of Jember M-Learning application.